A Review of the Nexus between Energy Consumption and Economic Growth in the BRICS Countries - Khobai, Hlalefang; Abel, sanderson; Le Roux, Pierre (International Journal of Energy Economics and Policy, 2021)
The study investigates the long run relationship and causal relationship between energy consumption and economic growth in the BRICS countries during the period 1990–2018. The Pedroni panel co-integration method is applied to analyse the co-integration relationship among the variables. The causality relationship among the variables is analysed using Pair-wise Granger-causality technique. The study’s results reveal that there is a long run relationship between economic growth, energy consumption, employment and trade openness in Brics countries. The research outcome further detected a unidirectional causality flowing from economic growth to energy consumption. This implies that the conservation policies that curb unnecessary loss in energy could be implemented in the BRICS countries without adversely affecting economic growth. Keywords: Energy consumption; Economic growth; Causality; BRICS countries JEL Classifications: D04, Q47, Q42, Q01 DOI: https://doi.org/10.32479/ijeep.6373